Studies of seed-borne fungi of tropical pasture legume species - Nik, WZ; Parbery, DG (CSIRO Publishing, 1977)
Fungi associated with seed of 22 tropical and three temperate pasture legume species were investigated and 42 species were isolated. Most species were obtained by using the blotter method, which required supplementing with procedures such as isolation onto potato dextrose agar and Nash-Snyder agar to ensure the isolation of as many species as possible from each seed sample. In order to isolate storage fungi, seeds were incubated on salt-malt agar. This medium was also effective in isolating pathogens which survived for long periods in seed, which suggests that such pathogens may share with storage fungi physiological characteristics which aid survival in seed. Eight species - Fusarium acuminatum, F. avenaceum, F. equiseti, F. fusarioides, F. oxysporum, F. poae, Diaporthe phaseolorum and Phoma sorghina - were proven pathogenic to a range of hosts, while four others - Botrytis cinerea, Cladosporium cladosporioides, Myrothecium leucotricha and an unidentified species of Fusarium - are regarded as possibly pathogenic and worth investigating. All species of Fusarium generally reduced emergence and root growth more than shoot growth although F. oxysporum reduced shoot growth more than emergence or root growth. F. equiseti was the most severe pathogen among the Fusaria and was also very common in seed samples. D. phaseolorum, not previously reported on Macroptilium, Stylosanthes or other leguminous hosts in Australia, caused serious damage to flowers and young pods, and seriously reduced seed set and altered the proportions of hard and soft seed in more mature infected pods. In infected pods most soft seed became infected and few infected seeds germinated. D. phaseolorum was isolated only from freshly collected seed, where it was present in embryo and cotyledonary tissue. P. sorghina caused leaf spotting and pod blight. Leaf infection caused reduction in root growth and a corresponding reduction in nodulation. Pod infections reduced seed set and produced a high proportion of infected seed. Infected seed generally failed to germinate. P. sorghina was also found in embryo and cotyledonary tissue and survived in infected seed for at least 5 years. One storage fungus, Aspergillus ruber, was a seed (embryo) pathogen. In freshly infected seed, germination resulted in abnormal seedlings. Seed infected for several months failed to germinate. Hard seed were generally free of storage and pathogenic fungi, while soft seed were commonly infected. Abnormal and damaged seed were the most likely to carry pathogens and other fungi.